Predictors of Multiple Sclerosis Severity Score in Patients with Multiple Sclerosis - Albatineh, Ahmed N. (Int J MS Care, 2020)
BACKGROUND: Multiple sclerosis (MS) is a demyelinating autoimmune disorder. Several factors have been shown to associate with MS clinical severity. The influence of different lifestyle factors on MS clinical severity as assessed by the Multiple Sclerosis Severity Score (MSSS) was investigated. METHODS: A questionnaire was administered to 128 Kuwaiti MS patients to assess the association of smoking, nutritional supplement use, food allergy, physical activity (PA), and educational level with MSSS. A multiple linear regression model was used to test for associations. Regression model results were adjusted for sex, history of blood transfusion, age at MS onset, and marital status. RESULTS: Smoking status, passive smoking, and food allergy are not associated with MSSS. Patients with MS with a college education and graduate/professional degrees score, on average, 2.56 lower on the MSSS compared with those with less than a high school education (β= −2.22, P = .045; and β = −2.90, P = .048, respectively). Patients who perform PA score, on average, 2.32 lower on the MSSS compared with those with no PA (moderate exercise, P = .003; rigorous exercise, P = .001), and PA correlated significantly with MSSS outcomes (r(2) = 0.452, P < .001). CONCLUSIONS: Educational level and PA are significantly associated with reduced MSSS, and both contribute to a less severe MS clinical course. Current MS management protocols should consider lifestyle changes to improve the quality of life of patients with MS.